Symbiodinium clades A and D differentially predispose Acropora cytherea to disease and Vibrio spp. colonization - Rouzé, Héloïse (Ecol Evol, 2016)
Coral disease outbreaks have increased over the last three decades, but their causal agents remain mostly unclear (e.g., bacteria, viruses, fungi, protists). This study details a 14‐month‐long survey of coral colonies in which observations of the development of disease was observed in nearly half of the sampled colonies. A bimonthly qPCR method was used to quantitatively and qualitatively evaluate Symbiodinium assemblages of tagged colonies, and to detect the presence of Vibrio spp. Firstly, our data showed that predisposition to disease development in general, and, more specifically, infection by Vibrio spp. in Acropora cytherea depended on which clades of Symbiodinium were harbored. In both cases, harboring clade D rather than A was beneficial to the coral host. Secondly, the detection of Vibrio spp. in only colonies that developed disease strongly suggests opportunistic traits of the bacteria. Finally, even if sporadic cases of switching and probably shuffling were observed, this long‐term survey does not suggest specific‐clade recruitment in response to stressors. Altogether, our results demonstrate that the fitness of the coral holobiont depends on its initial consortium of Symbiodinium, which is distinct among colonies, rather than a temporary adaptation achieved through acquiring different Symbiodinium clades.